High-heat-resistance polylactic acid material based on stereocomplex crystal and preparation method of high-heat-resistance polylactic acid material
Through the non-equal blending of medium and low molecular weight dextropolylactic acid and high molecular weight l-polylactic acid and ethylene-vinyl alcohol copolymer nucleating agent, the problem of poor heat resistance of polylactic acid materials is solved, and a high heat resistance of high heat resistance is prepared Composite polylactic acid materials are suitable for a variety of high-performance applications and reduce production costs and process complexity.
Patent Information
- Application Number
- CN202411342559.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-01-10
AI Technical Summary
Existing polylactic acid materials have problems such as poor heat resistance, slow crystallization kinetics, and brittle quality, which are difficult to widely use in the field of engineering plastics. The conventional modification methods are costly and complex, making it difficult to take into account the overall performance.
Using medium and low molecular weight dextropolylactic acid and high molecular weight l-polylactic acid, non-equal blending, ethylene-vinyl alcohol copolymer as nucleating agent, high heat resistance is prepared by melt blending, molding and annealing treatment. Stereoform composite polylactic acid material avoids the formation of homogeneous crystallization and improves the heat resistance of the material.
The heat resistance performance of polylactic acid materials has been improved. The Vica softening temperature is higher than 150℃. The material has good biodegradability and comprehensive performance. It is suitable for food packaging, automobiles and other fields. It has a simple process and low cost, which is suitable for industrialization. Large-scale application.
Smart Images

Figure CN119286210A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of polymer materials, and in particular to a high heat-resistant polylactic acid material based on stereocomplex crystallization and a preparation method thereof. Background Art
[0002] Non-degradable materials derived from fossil resources have a negative impact on the environment and human health, making the development and reuse of bio-based, biodegradable, and renewable plastic products a focus of attention. Polylactic acid is prepared from lactic acid or lactide, and the monomers come from renewable plants such as wheat and straw. Data from the cycle assessment research report show that the production of polylactic acid can reduce carbon dioxide emissions by 50-85% and energy consumption by 30-50%. It is currently the most affordable biodegradable polymer and is used in food packaging, biomedicine, engineering plastics and other industries. However, as a semi-crystalline polymer, polylactic acid has the disadvantages of being brittle, slow to crystallize, and poor heat resistance. Its crystallization kinetics are slower than those of polypropylene and polyethylene. Most polylactic acid products obtained using conventional processing procedures are amorphous. Therefore, when used as a plastic, the heat-resistant temperature is near its glass transition temperature (~60°C), resulting in a low market share of polylactic acid.
[0003] Therefore, expanding the application of polylactic acid through physical blending modification has become an increasingly active research topic. PLA materials are usually toughened with other biodegradable polyesters such as PBAT, PBS, PCL, etc., or their heat resistance is improved by filling starch, carbon nanotubes, etc. On the one hand, there are compatibility issues between biodegradable polyesters and polylactic acid, and the blending system needs to be further modified by volume expansion. On the other hand, although the addition of talcum powder, carbon nanotubes, etc. can improve the crystallization performance of polylactic acid and increase its heat resistance temperature, it is difficult to take into account the comprehensive performance of polylactic acid, and it is difficult to apply it to the field of engineering plastics, and there is a problem of high application cost. For example, the nucleating agent phenyl phosphate compound that promotes stereocomplex crystallization disclosed in application number CN201410475711.4 has a relatively complex preparation process and is expensive to synthesize (80,000 to 180,000 per ton).
[0004] Polylactic acid can be induced to form stereocomposite crystals by hydrogen bonding between poly-L-lactic acid and poly-D-lactic acid, and its melting point is about 50 degrees higher than the homogeneous crystals obtained by poly-L-lactic acid or poly-D-lactic acid crystallization, which is one of the effective methods for improving the heat resistance of polylactic acid. In addition, the formation of stereocomposite crystals can improve the mechanical properties, thermal hydrolysis resistance and solvent resistance of polylactic acid materials. Generally, the method for preparing stereocomposite crystals has solution casting and melt blending. Publication No. CN109337055A reports a method of using dichloromethane as a solvent to obtain stereocomposite polylactic acid by solution casting, but the obtained stereocomposite crystals have poor melt stability, and it is difficult to regenerate stereocomposite crystals after melting, and a large amount of solvent is used in the process.
[0005] During the melt processing, since the crystallization of poly-L-lactic acid and poly-D-lactic acid requires a longer diffusion path to obtain a stereocomposite, a high molecular weight blend with similar conventional linear molecular weight will form homogeneous crystals in addition to forming stereocomposite crystals during processing, and homogeneous crystals dominate, which leads to the performance of the poly-L-lactic acid / poly-D-lactic acid blend products obtained by melt processing cannot meet the actual application requirements. Publication No. CN111548504A discloses a method for preparing a stereocomposite polylactic acid material with excellent melt stability and melt processing performance by melt grafting reaction, but the grafting reaction may affect the degradation performance of polylactic acid. And most of the current research focuses on melt blending of PLLA and PDLA in a 50 / 50 ratio. The cost of D-lactide is higher than that of L-lactide, resulting in the production cost of the composite polylactic acid being higher than that of poly-L-lactic acid, which is also an obstacle to the widespread application of poly-L-lactic acid and poly-D-lactic acid blend materials.
[0006] Since low molecular weight polylactic acid is brittle, has poor mechanical properties, and is difficult to form a film, there is a technical misunderstanding in this field that a high-performance stereocomposite polylactic acid material is prepared by modifying PLLA and PDLA in equal proportions of high molecular weight. Therefore, the conventional practice is to melt blend high molecular weight PLLA and PDLA in a 50 / 50 ratio to prepare stereocomposite polylactic acid. However, this process often crystallizes to form a large number of homogeneous crystals. Too high a homogeneous crystal content will cause the purity of the polylactic acid stereocomposite crystal to decrease, and its heat resistance has not been improved. In addition, the processing temperature of high molecular weight PLLA and PDLA must be higher than 240°C. When processed at 220°C, a powder state is obtained. Only when processed above 240°C can a uniformly mixed product be obtained. Under this high temperature condition, molten polylactic acid is very prone to thermal degradation, which further reduces the performance of the material. Summary of the invention
[0007] In order to overcome the problems of the prior art, the present invention provides a high heat-resistant polylactic acid material based on stereocomplex crystallization, which uses medium and low molecular weight dextrorotatory polylactic acid to blend with high molecular weight l-lactic acid in non-equal proportions to finally obtain a high heat-resistant polylactic acid material, and homogeneous crystallization can be avoided during the production process.
[0008] To this end, the technical solution of the present invention is: a high heat-resistant polylactic acid material based on stereocomplex crystallization, comprising the following raw materials in weight percentage, which are prepared by mixing, molding and annealing:
[0009] Poly-L-lactic acid (PLLA), 40% to 90%;
[0010] Ethylene vinyl alcohol copolymer (EVOH), 5% to 50%;
[0011] Medium-low molecular weight poly (d-lactic acid) (PDLA), 5% to 10%; it acts as a nucleating agent;
[0012] The weight average molecular weight of the poly-L-lactic acid is in the range of 1.1×10 5 ~30×10 5 g / mol; the weight average molecular weight of medium and low molecular weight poly (d-lactic acid) is 7×10 3 g / mol~6×10 4 g / mol; the melt flow index of ethylene-vinyl alcohol copolymer is 1.6-4.4 g / 10 min under the measurement environment of melt temperature 190°C, die diameter 2.1 mm, and load 2.16 kg.
[0013] The melt flow index of ethylene-vinyl alcohol copolymer is measured as follows: ethylene-vinyl alcohol copolymer is melted into a fluid at 190°C, and then within 10 minutes, the melt is passed downward through a round tube with a diameter of 2.1 mm. A pressure of 2.16 kg is applied above the melt, and the gram weight of the melt flowing out from the bottom of the round tube is recorded, which is the melt flow index.
[0014] The above-mentioned method for preparing a high heat-resistant polylactic acid material based on stereocomplex crystallization comprises the following steps:
[0015] 1) Weighing the raw materials and placing them into a melt blending equipment for melt blending at a blending temperature of 190-220° C. for 5-10 minutes to obtain stereocomposite polylactic acid;
[0016] 2) Injection molding or hot pressing the stereocomposite polylactic acid, the injection molding or hot pressing temperature is 190-200°C;
[0017] 3) Annealing the formed material at a temperature of 140-170° C. for a time of 10-30 min to obtain the highly heat-resistant polylactic acid material.
[0018] Furthermore, the melt blending equipment is a torque rheometer, a single-screw extruder or a twin-screw extruder.
[0019] The above-mentioned high heat-resistant polylactic acid material based on stereocomplex crystallization is used in spinning, injection molding, vacuum forming, foaming molding, and extrusion molding processing techniques.
[0020] The high heat-resistant polylactic acid material of the present invention can be used in fields requiring high heat resistance of materials, such as clothing fabrics, food packaging, medical fabrics, and automobiles.
[0021] The present invention blends medium and low molecular weight dextrorotatory polylactic acid with high molecular weight l-lactic acid in non-equal proportions. On the one hand, by regulating the molecular weight of dextrorotatory polylactic acid, the ratio of homogeneous crystallization and stereocomposite crystallization in the blending system can be effectively regulated. On the other hand, when the non-50 / 50 ratio of PLLA and PDLA makes the content of stereocomposite crystallization reach a certain value, the stereocomposite crystallization forms an interconnected network channel in the polyl-lactic acid after annealing, greatly improving the overall heat resistance of the material. In addition, the stereocomposite crystallization can be used as a nucleating agent to promote the crystallization of polyl-lactic acid.
[0022] Compared with the prior art, the beneficial effects of the present invention are:
[0023] 1. The present invention breaks away from the conventional thinking of high molecular weight equal proportion PLLA and PDLA system, overcomes the technical prejudice in this field, and improves the heat resistance of polylactic acid at a lower cost by using medium and low molecular weight dextrorotatory polylactic acid and blending it with high molecular weight l-polylactic acid in non-equal proportions.
[0024] 2. In the heat-resistant polylactic acid material prepared by the present invention, poly (dextrorotatory lactic acid) is well dispersed in poly (l-lactic acid), and the content of the formed stereocomplex crystals is within a certain range. A network structure can be formed in the poly (l-lactic acid) matrix. The nucleation effect enables the material to obtain a heat-resistant polylactic acid material with a Vicat softening temperature higher than 150 degrees in a very short heat treatment time, and the modified polylactic acid material still has good biodegradability.
[0025] 3. The present invention combines the rigidity of polylactic acid with the excellent toughness and gas barrier properties of ethylene-vinyl alcohol copolymer to obtain a composite material with excellent comprehensive performance. At the same time, the heat resistance is improved by combining the processing method. The material has good application prospects in food packaging, electronic information, automobiles and other fields.
[0026] 4. The materials used in the present invention are all industrial raw materials, and the equipment used is mainly melt blending equipment. The process equipment is simple, the production cost is low, and it can be applied on an industrial scale, showing the important application prospect of stereocomplex crystallization in the thermal properties of polylactic acid. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 Partially annealed and unannealed polylactic acid blends.
[0028] Figure 2 It is the DSC (differential scanning calorimeter) curve of polylactic acid blend.
[0029] Figure 3 This is the Vicat softening temperature curve of some polylactic acid blends. DETAILED DESCRIPTION
[0030] The present invention is described below by means of specific embodiments.
[0031] Main raw material information:
[0032] PLLA (4032D), Natureworks LLC, USA, weight average molecular weight 1.1×10 5 g / mol; low molecular weight, medium molecular weight and high molecular weight PDLA are made in the laboratory. Low molecular weight PDLA: number average molecular weight 1.1×10 4 , weight average molecular weight 1.5×10 4 g / mol (PDI = 1.36);
[0033] Medium molecular weight PDLA: number average molecular weight 3.3×10 4 , weight average molecular weight 6×10 4 g / mol (PDI = 1.8); high molecular weight PDLA: number average molecular weight 11.5×10 4 , weight average molecular weight 18.9×10 4 g / mol (PDI=1.64).
[0034] The melt flow index of ethylene-vinyl alcohol copolymer (EVOH) is 1.6-4.4g / 10min (190℃, 2.16kg). If the melt flow index of ethylene-vinyl alcohol copolymer is too low, it may cause uneven mixing of materials during the blending process; if the melt flow index is too high, it will affect the heat resistance of the material. When measuring the melt flow index of ethylene-vinyl alcohol copolymer: ethylene-vinyl alcohol copolymer is melted into a fluid at 190℃, and then within 10 minutes, the melt is passed downward through a round tube with a diameter of 2.1mm, and a pressure of 2.16kg is applied above the melt. The gram weight of the melt flowing out from the bottom of the round tube is recorded, which is the melt flow index.
[0035] Example 1
[0036] 1) Melt blending
[0037] Poly-L-lactic acid and poly-D-lactic acid were fully dried at 80 degrees. Low molecular weight PDLA, PLLA and EVOH (melt index 1.6 g / 10 min (190°C, 2.16 kg)) with a weight ratio of 5:90:5 were put into a torque rheometer for melt blending under the following conditions: blending temperature of 190°C, blending time of 5 min, and blending speed of 60 rpm / min.
[0038] 2) Preparation of specimens
[0039] The obtained sample was added into a hot press, wherein the hot pressing temperature was 190° C., the hot pressing time was 5 min, the hot pressing pressure was 6 MPa, and cooled at room temperature.
[0040] 3) Annealing the sample
[0041] The hot-pressed specimens were annealed at 140°C for 30 min and then taken out for further experiments.
[0042] Example 2
[0043] The polylactic acid material was prepared in the same manner as in Example 1, except that the sample obtained by hot pressing was taken out after annealing at 170° C. for 10 min for further experiments.
[0044] Example 3
[0045] A polylactic acid material was prepared in the same manner as in Example 1, except that the weight ratio of PDLA, PLLA and EVOH was changed to 10:85:5.
[0046] Example 4
[0047] The polylactic acid material was prepared in the same manner as in Example 3, except that the sample obtained by hot pressing was taken out after annealing at 170° C. for 10 min for further experiments.
[0048] Example 5
[0049] 1) Melt blending
[0050] Poly-L-lactic acid and poly-D-lactic acid were fully dried at 80° C. Medium molecular weight PDLA, PLLA and EVOH (melt index 4.4 g / 10 min (190° C., 2.16 kg)) with a mass ratio of 5:80:15 were put into a torque rheometer for melt blending under the following conditions: blending temperature of 220° C., blending time of 8 min, and blending speed of 60 rpm / min.
[0051] 2) Preparation of specimens
[0052] The obtained sample was added into a hot press, wherein the hot pressing temperature was 220° C., the hot pressing time was 5 min, the hot pressing pressure was 6 MPa, and cooled at room temperature.
[0053] 3) Annealing the sample
[0054] The hot-pressed specimens were annealed at 140°C for 30 min and then taken out for further experiments.
[0055] Example 6
[0056] The polylactic acid material was prepared in the same manner as in Example 5, except that the sample obtained by hot pressing was placed in an oven at 170° C. for annealing for 10 min and then taken out for further experiments.
[0057] Example 7
[0058] A polylactic acid material was prepared in the same manner as in Example 5, except that the weight ratio of PDLA, PLLA and EVOH was changed to 10:75:15.
[0059] Example 8
[0060] The polylactic acid material was prepared in the same manner as in Example 7, except that the sample obtained by hot pressing was annealed at 170° C. for 10 min and then taken out for further experiments.
[0061] Example 9
[0062] 1) Melt blending
[0063] Poly-L-lactic acid and ethylene-vinyl alcohol copolymer were fully dried at 80 degrees. Low molecular weight PDLA, PLLA and EVOH (melt index 1.6 g / 10 min (190°C, 2.16 kg)) with a mass ratio of 5:45:50 were put into a torque rheometer for melt blending under the following conditions: blending temperature of 200°C, blending time of 5 min, and blending speed of 60 rpm / min.
[0064] 2) Preparation of specimens
[0065] The obtained sample was added into a hot press, wherein the hot pressing temperature was 200° C., the hot pressing time was 5 min, the hot pressing pressure was 6 MPa, and cooled at room temperature.
[0066] 3) Annealing the sample
[0067] The hot-pressed specimens were annealed at 170°C for 10 min and then taken out for further experiments.
[0068] Comparative Example 1
[0069] 1) Melt blending
[0070] Poly-L-lactic acid and poly-D-lactic acid were fully dried at 80 degrees. Low molecular weight PDLA, PLLA and EVOH (melt index 1.6 g / 10 min (190°C, 2.16 kg)) with a mass ratio of 5:90:5 were put into a torque rheometer for melt blending under the following conditions: blending temperature of 190°C, blending time of 5 min, and blending speed of 60 rpm / min.
[0071] 2) Preparation of specimens
[0072] The obtained sample was added into a hot press, wherein the hot pressing temperature was 190° C., the hot pressing time was 5 min, the hot pressing pressure was 6 MPa, and cooled at room temperature.
[0073] Comparative Example 2
[0074] A polylactic acid material was prepared in the same manner as in Comparative Example 1, except that the weight ratio of PDLA, PLLA and EVOH was changed to 10:85:5.
[0075] Comparative Example 3
[0076] 1) Melt blending
[0077] Poly-L-lactic acid and poly-D-lactic acid were fully dried at 80 degrees. Medium molecular weight PDLA, PLLA and EVOH (melt index 4.4 g / 10 min (190°C, 2.16 kg)) with a mass ratio of 5:80:15 were put into a torque rheometer for melt blending under the following conditions: blending temperature of 220°C, blending time of 8 min, and blending speed of 60 rpm / min.
[0078] 2) Preparation of specimens
[0079] The obtained sample was added into a hot press, wherein the hot pressing temperature was 190° C., the hot pressing time was 5 min, the hot pressing pressure was 6 MPa, and cooled at room temperature.
[0080] Comparative Example 4
[0081] A polylactic acid material was prepared in the same manner as in Comparative Example 3, except that the weight ratio of PDLA, PLLA and EVOH was changed to 10:75:15.
[0082] Comparative Example 5
[0083] 1) Melt blending
[0084] Poly-L-lactic acid and poly-D-lactic acid were fully dried at 80 degrees. High molecular weight PDLA, PLLA and EVOH (melt index 4.4 g / 10 min (190°C, 2.16 kg)) with a mass ratio of 5:85:10 were put into a torque rheometer for melt blending under the following conditions: blending temperature of 220°C, blending time of 8 min, and blending speed of 60 rpm / min.
[0085] 2) Preparation of specimens
[0086] The obtained sample was added into a hot press, wherein the hot pressing temperature was 190° C., the hot pressing time was 5 min, the hot pressing pressure was 6 MPa, and cooled at room temperature.
[0087] Comparative Example 6
[0088] A polylactic acid material was prepared in the same manner as in Comparative Example 5, except that the sample obtained by hot pressing was taken out after annealing at 140° C. for 30 min for further experiments.
[0089] Comparative Example 7
[0090] A polylactic acid material was prepared in the same manner as in Comparative Example 5, except that the sample obtained by hot pressing was taken out after annealing at 170° C. for 10 min for further experiments.
[0091] Comparative Example 8
[0092] A polylactic acid material was prepared in the same manner as in Comparative Example 5, except that the weight ratio of PDLA, PLLA and EVOH was changed to 10:80:10.
[0093] Comparative Example 9
[0094] The polylactic acid material was prepared in the same manner as in Comparative Example 8, except that the sample obtained by hot pressing was annealed at 140° C. for 30 min and then taken out for further experiments.
[0095] Comparative Example 10
[0096] The polylactic acid material was prepared in the same manner as in Comparative Example 8, except that the sample obtained by hot pressing was annealed at 170° C. for 10 min and then taken out for further experiments.
[0097] Comparative Example 11
[0098] 1) Melt blending
[0099] Poly-L-lactic acid and ethylene-vinyl alcohol copolymer were fully dried at 80 degrees. PLLA and EVOH (melt index 4.4 g / 10 min (190°C, 2.16 kg)) with a mass ratio of 75:25 were put into a torque rheometer for melt blending under the following conditions: blending temperature of 190°C, blending time of 5 min, and blending speed of 60 rpm / min.
[0100] 2) Preparation of specimens
[0101] The obtained sample was added into a hot press, wherein the hot pressing temperature was 190° C., the hot pressing time was 5 min, the hot pressing pressure was 6 MPa, and cooled at room temperature.
[0102] Comparative Example 12
[0103] The poly-L-lactic acid was fully dried at 80 degrees. The PLLA was added into a hot press, wherein the hot pressing temperature was 190 degrees Celsius, the hot pressing time was 5 minutes, the hot pressing pressure was 6 MPa, and cooled at room temperature.
[0104] Comparative Example 13
[0105] The polylactic acid material was prepared in the same manner as in Comparative Example 12, except that the sample obtained by hot pressing was annealed at 140° C. for 30 min and then taken out for further experiments.
[0106] Comparative Example 14
[0107] The polylactic acid material was prepared in the same manner as in Comparative Example 12, except that the sample obtained by hot pressing was annealed at 170° C. for 10 min and then taken out for further experiments.
[0108] The crystallization performance test method is: using DSC test, nitrogen atmosphere, to carry out initial thermal performance test, the sample is heated from 25°C to 250°C at 10°C / min to test the melting behavior.
[0109] Vicat softening temperature test method: The polylactic acid composite material prepared above is hot-pressed for 5 minutes at 190°C-220°C and 6MPa in a hot press using a mold of a certain specification to form a standard specimen of 10mm×10mm×3mm required for the test. After annealing under different conditions, the Vicat softening temperature is tested.
[0110] Figure 1 The figure is a physical state diagram of each embodiment and comparative example after different heat treatment conditions (the "low D" in the figure represents low molecular weight PDLA, and "low D5%" represents the addition of 5wt% low molecular weight PDLA). It can be seen from the figure that the material turns white after heat treatment at 140°C because the heat treatment increases the crystallinity of the polylactic acid material; at the same time, after heat treatment at 170°C, Example 6, Comparative Examples 7 and 14 all show different degrees of melting.
[0111] pass Figure 2 It can be seen from the DSC curve that both the untreated comparative examples 2 and 8 showed obvious crystallization peaks when heated, while no crystallization peak was observed in the example 3 annealed at 140°C. The crystallization peak of the example 4 annealed at 170°C was significantly lower than that of the comparative example 2, but the crystallization peak of the comparative example 10 under the same conditions did not change significantly compared with the comparative example 8, indicating that the low molecular weight PDLA is more conducive to accelerating crystallization, and the efficiency of improving the crystallization performance of poly-L-lactic acid is higher than that of the high molecular weight PDLA. In addition, the area ratio of the stereocomplex crystallization melting peak to the homogeneous crystallization melting peak of the DSC curve shows that when the low molecular weight PDLA is added, the content of stereocomplex crystals in the material is significantly higher than that of the PLA composite material with the addition of high molecular weight PDLA. The melting point of SC crystals is between 210 and 230°C, which is higher than the melt mixing and processing molding temperature. It can be used as an efficient nucleating agent to accelerate the crystallization of the matrix during the melt cooling process and improve the crystallinity of the material or product.
[0112] Figure 3It is a strain-temperature diagram of some embodiments and comparative examples. According to the test conditions, the temperature when the strain reaches 33.3% (at the dotted line) is the Vicat softening temperature of the material. It can be seen that when the temperature is close to the Vicat softening temperature, the strain of the material will increase sharply and lose mechanical properties. The Vicat softening temperature test results of Examples 1-8 and Comparative Examples 6-9 show that the effect of low molecular weight and medium molecular weight PDLA in improving heat resistance is better than that of high molecular weight PDLA. By comparing Example 2 with Comparative Example 1, Examples 3 and 4 with Comparative Example 2, Example 5 with Comparative Example 3, and Examples 7 and 8 with Comparative Example 4, it can be seen that the heat resistance of the PLA composite material after annealing is better than that of the PLA composite material without annealing, and its Vicat softening temperature is above 150°C, which can be used as an excellent bio-based degradable heat-resistant material.
[0113] Therefore, poly (L-lactic acid) / ethylene-vinyl alcohol copolymer and medium- and low-molecular-weight poly (D-lactic acid) can be mixed, molded, and annealed to produce a material with excellent heat resistance (Vicat softening temperature is 150°C).
[0114] Table 1: Thermal performance data of each embodiment and each comparative example
[0115]
[0116]
[0117] Note: - indicates that the sample was damaged during the test and the test result could not be obtained; * indicates that the sample melted or deformed during the heat treatment process
[0118] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art. The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiments according to the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A high heat-resistant polylactic acid material based on stereocomplex crystallization, characterized in that: The raw materials comprising the following weight percentages are mixed, formed and annealed to obtain the product: Poly-L-lactic acid, 40%~90%; Ethylene-vinyl alcohol copolymer, 5%~50%; Medium and low molecular weight poly (D-lactic acid), 5% to 10%; The weight average molecular weight of the poly-L-lactic acid is in the range of 1.1×10 5 ~30×10 5 g / mol; the weight average molecular weight of medium and low molecular weight poly (d-lactic acid) is 7×10 3 g / mol~6×10 4 g / mol; the melt flow index of ethylene-vinyl alcohol copolymer is 1.6~4.4g / 10min under the measuring environment of melt temperature 190℃, die diameter 2.1mm and load 2.16kg.
2. The method for preparing a high heat-resistant polylactic acid material based on stereocomplex crystallization according to claim 1, characterized in that The steps include: 1) After weighing the raw materials, put them into a melt blending equipment for melt blending at a blending temperature of 190-220°C for 5-10 minutes to obtain stereocomposite polylactic acid; 2) Injection molding or hot pressing the stereocomposite polylactic acid at a temperature of 190-200°C; 3) Annealing the formed material at a temperature of 140-170° C. for a time of 10-30 min to obtain the highly heat-resistant polylactic acid material.
3. The method for preparing a high heat-resistant polylactic acid material based on stereocomplex crystallization according to claim 2, characterized in that: The melt blending equipment is a torque rheometer, a single-screw extruder or a twin-screw extruder.
4. The use of a high heat-resistant polylactic acid material based on stereocomplex crystallization according to claim 1, characterized in that: Used in spinning, injection molding, vacuum forming, foaming and extrusion molding processes.
Citation Information
Patent Citations
Preparation method of high-molecular polylactic acid (PLA) three-dimensional composite material capable of being crystallized rapidly
CN104262917A
Preparation method of stereocomplex crystallization type polylactic acid block polymer
CN109337055A
Stereo-complex polylactic acid material or product with excellent melt stability and melt processability and preparation method thereof
CN111548504A